2014
DOI: 10.1002/btpr.1907
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the effects of postinduction glutamine feeding on the growth and productivity of CHO cells

Abstract: Inducible mammalian expression systems are increasingly being used for the production of valuable therapeutics. In such system, maximizing the product yield is achieved by carefully balancing the biomass concentration during the production phase and the specific productivity of the cells. These two factors are largely determined by the availability of nutrients and/or the presence of toxic waste metabolites in the culture environment. Glutamine is one of the most important components of cell culture medium, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…(d) The H + concentration inside the cell is reduced. This is supported by metabolic profiling data which show accumulation of alanine(Sheikholeslami, Jolicoeur, & Henry, 2014;Zhang, Shen, & Zhang, 2004) which sometimes undergoes its own metabolic shift similar to that of lactate(Ma et al, 2009). Lactate is transported alongside protons into the cell, despite a lactate gradient not being present.…”
mentioning
confidence: 76%
“…(d) The H + concentration inside the cell is reduced. This is supported by metabolic profiling data which show accumulation of alanine(Sheikholeslami, Jolicoeur, & Henry, 2014;Zhang, Shen, & Zhang, 2004) which sometimes undergoes its own metabolic shift similar to that of lactate(Ma et al, 2009). Lactate is transported alongside protons into the cell, despite a lactate gradient not being present.…”
mentioning
confidence: 76%
“…D the osmolality values of the control cultures and cultures at elevated pCO 2 started to diverge after the metabolic shift and increased osmolality is known to potentially affect cell metabolism. Since glutamine metabolism has been shown before to correlate with the lactate metabolic shift in the batch cultivations and other studies and furthermore ammonia metabolite profiles were strongly different between cultures at low and high pCO₂, the role of glutamine was investigated in more detail. Differences in the ammonia profiles could be directly linked to variations in the specific glutamine consumption rate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that COMPLETE-MFA can significantly improve not only flux precision but also flux observability in complex network models (Crown and Antoniewicz, 2013a). Parallel labeling experiments are also increasingly used for validation of metabolic network models, including in microbial (Au et al, 2014; Leighty and Antoniewicz, 2012), mammalian (Ahn and Antoniewicz, 2013; Sheikholeslami et al, 2014), and plant systems (Allen and Young, 2013; Alonso et al, 2007; Schwender et al, 2006). …”
Section: Introductionmentioning
confidence: 99%